The conditional effects of income inequality on extreme right wing votes: A subnational analysis of Western Europe in the 1990s - David Jesuit; Vincent Mahler; Piotr Paradowski (Luxembourg Income Study (LIS), 2008)
This paper addresses two major limitations of cross-national research on electoral support for extreme right parties (ERPs) in Western Europe: its almost exclusive focus on national-level data and its failure to examine the role of the social welfare state and social capital. We employ Tobit I estimations in an additive and interactive model and compute conditional coefficients and standard errors for several interactive variables. We conclude that the interactive model offers more explanatory power than the additive and that levels of social capital play a major role in mediating the relationships between immigration, unemployment and support for ERPs.
Keywords: 330; political parties; right wing politics; elections; immigration politics; income inequality; Wahlverhalten; Radikalismus; Migrationspolitik; Einkommensverteilung; EU-Staaten